Fiscal Decentralization, Expenditure Autonomy as the Mediating Mechanism and Economic Growth: Maqasid Syariah Perspective - Rieska Karunia Ramadhani; Susilo; Nugroho Suryo Bintoro; Lalang Saksono (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Fiscal decentralization has reshaped Indonesia’s regional governance, aiming to boost economic growth through local autonomy. This study investigates how locally generated revenue and central government transfers influence regional economic growth through expenditure autonomy, emphasizing ethical principles like wealth preservation and public welfare. Using path analysis on data from 38 provinces over 2020-2024, the research examines direct and mediated effects of revenue sources on economic outcomes. Locally generated revenue significantly drives growth, while central transfers only contribute when channelled through strategic spending, with expenditure autonomy mediating both effects. These findings highlight the critical role of targeted budget allocation in maximizing economic impact. The study concludes that aligning fiscal policies with ethical principles can foster equitable development across Indonesia’s diverse regions. Policymakers should reform transfer mechanisms to prioritize performance-based allocations and strengthen local capacity to enhance expenditure efficiency, though limitations like inconsistent data quality and pandemic disruptions suggest caution in generalizing results. Future research could explore sector-specific spending to further optimize decentralization.